Oral manifestations of neurological disorders: A key note - Wahi, Saurabh; Singh, Shailendra; Wahi, Shradha; Kumar, Prince (Nigerian Journal of Basic and Clinical Sciences, 2026)
Sir,The central nervous system and oral cavity have a close anatomical location. At this time, diseases of central nervous system have been extensively studied in various specialties of biomedical sciences like otology, ophthalmology, neurology,neurosurgery, and dentistry. Identification of orofacial manifestations of central nervous system is usually in a direct relation with the liabilities of a dental surgeon. Preventive dental care for patients with neurological disorders needsa specific approach, because of the fact that these patients belong to the category of patients with special needs; all kind of preventive and rehabilitative treatments necessitates well‑planned and specific approaches.[1] Neurological disorders affect the orodental tissues in different ways. As mentioned, the common neurocutaneous (phakomatosis) diseases include Sturge‑Weber syndrome, tuberous sclerosis, neurofibromatosis of Von Recklinghausen and incontinentiapigmenti. These diseases frequently remain unnoticeable, but have significant direct relationship to oral cavity and orofacial structures.[2] Oral environment may also be severely altered by neoplasias of orofacial nerves and their sheaths (e.g., neurofibroma, neurolemmoma, traumatic neuroma, malignant schwannoma), cranial nerve tumors with orofacial affections (e.g., trigeminal neurinoma, acoustic neurinoma, and olfactory neuroblastoma), and systemic tumors withsignificant neural and orofacial symptoms (e.g., Gardner’s syndrome and multiple endocrine neoplasia syndromes).